Gait initiation and partial body weight unloading for functional improvement in post-stroke individuals - Gama, Gabriela L.; Celestino, Melissa L.; Barela, Jose A. [UNESP]; Barela, Ana M. F. (Elsevier B.V., 2019)
Background: To better understand gait initiation in individuals with stroke and suggest possible training strategies, we compared the gait initiation of individuals with stroke and age-matched controls, and we examined the influence of different amounts of body weight support (BWS) during the execution of gait initiation in individuals with stroke. Materials and methods: Twelve individuals with stroke and 12 age-matched controls initiated gait after a verbal command at a self-selected and comfortable speed, and individuals with stroke also initiated gait wearing a harness with 0%, 15%, and 30% of BWS. Length and velocity of the first step, distance between heels, and weight bearing in both lower limbs in the initial position were calculated. We also assessed the displacement and average velocity of the center of pressure (CoP) in the medial-lateral (ML) and anterior-posterior (AP) directions in 3 distinct sections during gait initiation, which correspond to the CoP position toward the swing limb, stance limb and progression line, respectively. Results: Individuals with stroke presented shorter and slower step, shorter and slower CoP-ML and CoP-AP toward swing limb and Cop-ML towards stance limb, and longer and faster CoP-AP toward stance limb compared to their peers. The BWS lead individuals with stroke to decrease step length and to increase CoP-ML displacement and average velocity toward stance limb. Conclusion: Individuals with stroke present impairments in executing gait initiation mainly during the preparation period and the employment of an overground BWS system promotes a better performance. These results suggest that BWS is a functional strategy that enables individuals with stroke to modulate gait initiation and it could be adopted for gait intervention.
Keywords: Overground body weight support system; Force plate; Center of pressure; Hemiparesis